2017
DOI: 10.1002/iub.1689
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus‐mediated human aquaporin‐1 expression in hepatocytes improves lipopolysaccharide‐induced cholestasis

Abstract: Lipopolysaccharides (LPS) are known to cause cholestasis in sepsis. There is evidence that a defective expression of canalicular aquaporin water channels contributes to bile secretory failure in LPS-induced cholestasis. Thus, we studied whether the hepatic adenovirus-mediated transfer of human aquaporin-1 gene (haqp1) can improve the cholestasis induced by LPS. Adenoviral vector encoding hAQP1 (AdhAQP1) or control vector was administered to rats by retrograde intrabiliary infusion. Hepatocyte canalicular hAQP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…It is possible that even an excessive increase in body weight, as was the case for our proband, can increment the predisposition to cholestasis. As to intermittent cholestasis associated to ATP8B1, bacterial endotoxins such as lipopolysaccharides released from sites of infection [20] might induce the failure of bile transport, thus explaining intermittent cholestasis. Therefore, drugs that act on the transport of bile salts may prevent the occurrence of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that even an excessive increase in body weight, as was the case for our proband, can increment the predisposition to cholestasis. As to intermittent cholestasis associated to ATP8B1, bacterial endotoxins such as lipopolysaccharides released from sites of infection [20] might induce the failure of bile transport, thus explaining intermittent cholestasis. Therefore, drugs that act on the transport of bile salts may prevent the occurrence of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some reports have shown that AQP1 induction decreases in ammation and apoptosis in hepatic and pulmonary injuries. Hepatocyte-induced AQP1 using adenovirus improves estrogen-induced and lipopolysaccharide-induced cholestasis in rats (31)(32)(33). Alpinetin, a Chinese medicine, alleviates lung AQP1 levels (34).…”
Section: Discussionmentioning
confidence: 99%
“…SL decreases plasma membrane fluidity, as a result of an increase in cholesterol and a decrease in phospholipids [46]. On the other hand, LPS treatment decreases cholesterol content in the canalicular membrane [47], an effect that could have been counteracted by SL co-treatment. SL effect would enable the stabilization of the transporters in lipid raft microdomains, thus preventing their transfer to non-raft structures, and their further endocytosis via a clathrin-dependent mechanism [48].…”
Section: Discussionmentioning
confidence: 99%